Analysis of the Infiltration of Slang Through the Social Media Platform TikTok in Indonesian Language Instruction at Jati 2 Public Elementary School - Siva Hidayatul Qirom; Eka Budhi Santosa; Septi Yulisetiani (Journal of Educational Sciences, 2026)
The increasing use of the social media platform TikTok among elementary school students has triggered a shift in language use from standard Indonesian to slang, which has the potential to affect language proficiency and character development. This study aims to analyze the infiltration of slang through TikTok in character-based Indonesian language instruction at SD Negeri Jati 2. The study employs a descriptive qualitative approach with observation, interviews, and documentation involving students, teachers, and parents. The results indicate that TikTok significantly influences students’ language style, marked by increased use of slang and the adoption of vocabulary and expressions from social media. Some examples of evolving slang terms include hits, worth it, bestie, gas, auto, spill, relate, FYP, at least, and OOTD. To address this, teachers implemented the habit of using standard language, modeling proper language use, reprimands, and the integration of character values into the learning process. Thus, the infiltration of slang can be controlled through the strengthening of character education and the cultivation of proper and correct Indonesian language use with the support of teachers and parents. This study makes  important contribution and provides more specific analysis of elementary school students and their integration with character-building efforts.